Safety of Continuous Infusion Ketorolac in Postoperative Coronary Artery Bypass Graft Surgery Patients - Howard, Meredith L. (Pharmacy (Basel), 2016)
Background:Continuous infusion ketorolac is sometimes utilized for analgesia in postoperative coronary artery bypass graft (CABG) patients despite contraindications for use. Limited literature surrounds this topic; therefore, this study was conducted to evaluate the safety of this practice. Methods: This retrospective cohort study evaluated the primary outcome of mortality and secondary outcomes of incidence of bleeding and myocardial infarction (MI). All patients who underwent isolated CABG surgeries and received continuous infusion ketorolac during the study period were included. An equal number of randomly selected isolated CABG patients served as control patients. Electronic medical records and the Society of Thoracic Surgeons (STS) database were utilized to determine baseline characteristics and outcomes; Results: One hundred and seventy-eight patients met inclusion; 89 in each group. More patients in the control group underwent on-pump surgeries (78.6% vs. 29.2%, p = 0.01) and had higher STS risk scores (1.1% vs. 0.6%, p = 0.003). There was no difference in mortality between the ketorolac group and control group (2.2% vs. 3.3%, p = 0.605). Additionally, no patients experienced a MI and there was no difference in bleeding incidence (5.5% vs. 6.7%, p = 0.58); Conclusions: No association was found between continuous infusion ketorolac and increased risk of mortality, MI, or bleeding events in postoperative CABG patients. Considerations to differences in baseline characteristics must be made when interpreting results.